Employee Perceptions About the Impact of Supervisor Leadership Styles (LS) on Their Level of Engagement (Journal of Leadership, Accountability and Ethics, 2022)
The perceptions held by subordinates in three departments (Finance, Human Resource and Marketing), located at the Head office of a Caribbean retail giant, about the Leadership Styles (LSs) of their immediate supervisors, in reference to their levels of engagement, were researched using a Quantitative methodology and a Survey research design. The electronically administered, researcher-developed questionnaire, comprised thirty-six questions and, included questions from the Utrecht Work Engagement Scale (UWES). Of a population of 175, a sample of 75 employees were surveyed however, the response rate was 44%. Pearson’s correlation coefficient (R), Regression and ANOVA were the statistical tests employed to analyse data and test the Hypotheses. Both Null hypotheses were rejected; the main findings were that there is a relationship between supervisor LSs and Employee Engagement (EE) and, employee length of service and engagement; the LSs of immediate supervisors were perceived as Authoritative among other undesirable types and; though employees felt engaged at times, they believed their engagement levels could be improved with better supervisory and managerial leadership efforts and practices.
Keywords: leadership; accountability; ethics; supervisor leadership styles; employee engagement levels; employee perceptions; Caribbean; Utrecht Work Engagement Scale (UWES)